ANALISIS PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA UNTUK MENINGKATKAN KINERJA KARYAWAN : (Studi Kasus Pada RS Roemani Semarang) - Ratna Kusumawati (Universitas Wahid Hasyim, 2008)
Medical services industry has become more competitive nowadays. This made hospitals need to improve their performance. Roemani Hospital in Semarang is not an exception. One effort that can be done is to improve the performance of the employees through employee’s Job satisfaction. This research evaluates the effect of Organizational Culture and Leadership Style on Employee’s Job Satisfaction that influence the Employee’s performance.To test the issue, data was collected by distributing questionnaires to 110 employees of Roemani Hospital in Semarang. The data acquired was analyzed using the Structural Equation Model (SEM). From the result of this analysis, the Structural Equation Model has fulfilled the Goodness of Fix Index criteria: chi square = 106.716, probability = 0.649, RMSEA = 0.000, GFI = 0.892, AGFI = 0.854, CFI = 1.000.The analysis result shows that Organizational Culture positively and significantly affect the Job Satisfaction that positively and significantly affect the performance, Organizational Culture positively, significantly and directly affect the Performance, The Leadership Style positively and significantly affect the performance both directly and indirectly through Job Satisfaction.Based on the results, managerial implication suggest that improvement of the job satisfaction and performance can be achieved by establishing and treasuring the involvement culture, and having a participative leadership style align with giving salaries that is considered satisfying .Key words : organizational culture, leadership style, job satisfaction, performance